Näringsbelastning på en anlagd våtmark från åker, skog och enskilda avlopp - Karlsson, Marie (2005)
This work is a part of the project "Våtmarker i odlingslandskapet – uppföljning av miljömålen" (Wetlands in arable land – following-up of the environmental goals). The main objective with this project is to study nitrogen and phosphorus retention in a constructed wetland by using mass balance calculations. Continuous measurements of nutrients and water flow through the inlet and the outlet of the wetland are made. However, substantial amounts of nitrogen and phosphorus were assumed to reach the wetland with a drain-pipe transporting wastewater from nearby houses (10 persons). This drain-pipe is located after the inlet and in order to make reliable mass balance calculations it was important to quantify this flow of nutrients through measurements, which was the main objective with this thesis. Another objective was to quantify nitrogen and phosphorus load from forest and arable land by using literature and a nitrogen leaching model. The aim was also to describe how water moves through the catchment toward the wetland.